ELECTRONIC SYSTEM DESIGN ANALYSIS SERVICES Present List BEKERJADI CNOOC SES, LTD JAKARTA - Mulyanto Mulyanto; Drs. Sunarto Usna, MMSI (Jurnal Sistem Informasi, 2006)
At CNOOC SES, Ltd. as mining companies oil and gashas locations scattered work-in Jakarta and the waters around the IslandsA thousand-with the number of workers tetapnyayang reach approximately 850 people wheremore than 60% workers in offshore, then implementing a computerized systemvery appropriate. To that end, in all departments has been equipped with facilitiescomputers to process and process complex data and require a processfast. Personnel Administration Department under the Human divisionResources and Support Service plays an important role in controlling andprocessing of electronic services present a list of workers, so that the computerized systemThis addition can improve work efficiency and effectiveness may also increasedata accuracy.View of these problems, the author tries to describe andimplement in a report that mengambiljudul NOA: "ANALYSISSYSTEM DESIGN SERVICE WORKER present ELEKTRONIKDAFTARIN CNOOC SES, LTD JAKARTA ".